2018
DOI: 10.1007/s00784-018-2608-6
|View full text |Cite
|
Sign up to set email alerts
|

Free gingival graft adjunct with low-level laser therapy: a randomized placebo-controlled parallel group study

Abstract: Low-level laser therapy reduced the shrinkage of free gingival graft's surface area after 6 months and enhanced postoperative pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 39 publications
0
36
0
6
Order By: Relevance
“…In our study, the recipient bed was prepared with connective tissue left on the periosteum. When the GT was 1.5–2 mm, no complaints were caused by palatinal area postoperatively.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In our study, the recipient bed was prepared with connective tissue left on the periosteum. When the GT was 1.5–2 mm, no complaints were caused by palatinal area postoperatively.…”
Section: Discussionmentioning
confidence: 88%
“…Graft shrinkage can be evaluated during the early healing period or in the late period . There are conflicting studies reporting that graft shrinkage continues until 6 months or that graft sizes do not change between 1 and 6 months postoperatively . Based on the knowledge that the maturation of the graft lasts until the 5th month, we performed our analysis at the 6th postoperative month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several features were suggested as risk factors for the outcomes of FGG; these include but are not limited to: improper preparation of the recipient site, inadequate graft size and thickness, poor adaptation to the recipient bed and failure to stabilize the graft . As it has been shown that FGG undergoes a significant shrinkage (around 30%) during the healing process, a graft wider than the site needing soft tissue augmentation has to be harvested, and this may account for the postoperative discomfort and complications reported at the donor site . More recently, several authors have focused on the shrinkage of FGG compared with apically positioned flap alone or graft substitutes, such as collagen matrix or acellular dermal matrix (ADM) .…”
Section: The Free Gingival Graftmentioning
confidence: 88%
“…During the first stage, 104 studies were excluded based on the evaluation of titles and abstracts (inter-reviewer agreement, kappa statistic = 0.92). Second, after screening the full-text articles of the remaining 23 studies, 13 studies were excluded because of inappropriate study design [15][16][17][18][19][20] and irrelevant outcome measurement [21][22][23][24][25][26][27] (S1 Table) and 10 eligible studies [28][29][30][31][32][33][34][35][36][37] (five for HLLT, four for PBMT, and one for both HLLT and PBMT) were included in this systematic review (interreviewer agreement, kappa statistic = 0.91). Of these, four studies [29,31,33,34], which showed adequate continuous data concerning the pain level measured with VAS score, were included in the meta-analysis.…”
Section: Search and Selection Resultsmentioning
confidence: 99%